2019
DOI: 10.1007/s10450-019-00044-2
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption mechanism of poly(vinyl alcohol) on the surfaces of synthetic zeolites: sodalite, Na-P1 and Na-A

Abstract: The structure of poly(vinyl alcohol)-PVA layers adsorbed on the synthetic zeolites surfaces was determined. Three zeolites: sodalite, Na-P1 and Na-A were obtained using hydrothermal conversion of fly ash with aqueous sodium hydroxide. The effects of solution pH and zeolite type on the adsorption mechanism of the polymer were examined. The analysis of the results obtained by means of spectrophotometric and microelectrophoretic measurements as well as potentiometric titrations enabled description of interfacial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…This is mainly due to the overlapping of the diffusion parts of the electrical double layer formed on the opposite walls inside the relatively small solid pores. Such behavior was also observed for suspensions containing other zeolites [ 58 , 59 , 60 ].…”
Section: Resultssupporting
confidence: 61%
“…This is mainly due to the overlapping of the diffusion parts of the electrical double layer formed on the opposite walls inside the relatively small solid pores. Such behavior was also observed for suspensions containing other zeolites [ 58 , 59 , 60 ].…”
Section: Resultssupporting
confidence: 61%
“…Figure 2 shows the changes in the values of this parameter as a function of the solution pH for the Na-A samples dispersed in water and aqueous solutions of AN PAM, CT PAM, phosphate(V) ions, as well as mixed solutions of both adsorbates, i.e., AN PAM + phosphate(V) ions and CT PAM + phosphate(V) ions. The analysis of these curves indicated that the point of zero charge (pzc) of synthetic aluminosilicate is at pH of about 10 ( Wiśniewska et al 2019). This means that in a solution of pH 10, the zeolite has the surface charge equal to zero (the concentrations of the positively and negatively charged surface groups are the same).…”
Section: Resultsmentioning
confidence: 99%
“…The surface charge density (σ 0 ) and zeta potential (ζ) as a function of solution pH (Wiśniewska et al 2019) were determined at 25 °C in the following systems:…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy to mention that zeolites can be directly synthesized from raw materials (e.g., mineral clays) or industrial waste (e.g., fly ash) by means of hydrothermal transformation with a wide range of applications in adsorption and separation processes. Although this synthetic protocol is not in the scope of our review, it is a very useful technique that can diminish the negative impacts of industrial wastes on the environment [51][52][53]. In addition, the incorporation of heteroatoms in a metal-zeolite framework (e.g., Ni-MFI topology) rather than conventional Al-containing zeolites needs the synthesis technique, which is modified by altering pH and the type of precursors as the interaction of heteroatoms with organic SDA can differ from Al and Si [54].…”
Section: Introductionmentioning
confidence: 99%